Implementasi Dana ZIS Melalui Progam Bedah Rumah Tidak Layak Huni (Studi BAZNAS Kabupaten Malang) - Romadlon Chotib; Evi Mahirotus Zakiah (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
The  activity is a form  collaboraation of between academics at the Raden Rahmat Islamic University of Malang and the BAZNAS institution in Malang Regency. In this discussion, we can see how the house renovati of   programm caried out by baznas Malang regency. Is implemented and see the level of effectiveness in improving welfare of the people who receive the aid funds. The aim off a discussion surgery program was implemented and how effective the home surgery program was. In collecting data using the Qualitative method, to collec data and informasii from means of the observati and interview.  Results of a discussion were the implementati of the house renovation program, namely baznas compiled, created a program and budget for the house renovation. Mustahik candidates are required to fulfill the requirements of the Baznas institution. mustahiq getsa Rp. 12,500,000 from these fund mustahiq must be clever in managing the funds provided. Organitation of baznas does no determine  shape at  house be built